Synthesis and Anticancer Activities of Novel Bis-chalcones Incorporating the 1,3-diphenyl-1H-pyrazole Moiety: In Silico and In Vitro Studies - Mohamed, Magda F.; Sroor, Farid M.; Elsayed, Shahinda E.; Mahrous, Karima F.; Mageed, Lamiaa; Hanafy, Mahmoud K.; Ibrahim, Sherif A.; Elwahy, Ahmed H. M.; Abdelhamid, Ismail A. (Letters in Drug Design & Discovery, 2022)
A new series of bis-chalcones 5-10 has been prepared by the condensation reaction of one equivalent of bis(acetophenones) 3a-f with two equivalents of 1,3-diphenyl-1H-pyrazole-4-carbaldehyde 4. The newly prepared compounds 5-10 have been fully characterized and evaluated as in vitro anticancer agents against a panel of human cancer cell lines A431, A549, PC3, and a normal human skin fibroblast BJ1. Aims: The current work is designed to explore the anti-cancer activity of novel bis-chalcones incorporating a 1,3-diphenyl-1H-pyrazole moiety. Background: Chalcones represent one of the most important organic compounds that have been attracting the interest of many researchers in drug discovery. Objective: The present study was carried out to explore anti-cancer activity of novel bis-chalcones incorporating a 1,3-diphenyl-1H-pyrazole moiety as in vitro and in silico studies. Materials and Methods: We used the condensation reaction to prepare bis-chalcones incorporating 1,3- diphenyl-1H-pyrazole moiety. The MTT Assay, Anti-cancer activity, Gene expression, DNA Fragmentation, DNA Damage, and Molecular docking were investigated. Results: Compounds 5 and 9 were found to be the most promising compounds in the prepared series with IC50 (50.3 and 50.1 μg/ml, respectively) against epidermoid cancer cell line A431 compared to doxorubicin as a reference drug. Conclusion: All of these results showed that chalcones 5 and 9 have promising anti-cancer properties without cytotoxic effect, which could make them a promising active component for further studies.
Keywords: anti-cancer